Challenges of managing diabetes in Iran: meta-synthesis of qualitative studies - Mohammad Mohseni (BMC Health Services Research, 2020)
Abstract Background Although several diabetes management and control programmes are introduced in Iran, many patients do not achieve diabetes-related clinical goals as recommended. The aim of this study was to identify the qualitative evidence for the challenges regarding diabetes management. Methods A systematic review of qualitative studies following PRISMA guidelines was undertaken. Scopus, PubMed, Science Direct, and Web of Knowledge were searched as well as Persian databases including Magiran, Irandoc and SID from inception to August 2019. The included Studies were either in English- or Persian-language qualitative studies reporting the perspectives of patients, their relatives, or healthcare service providers. Content of the findings were analysed and organized according to Chronic Care Model framework. Results Twelve studies met the inclusion criteria. Six main themes were identified including holistic understanding of patients, leadership and governance difficulties, service delivery, workforce, financing, and information and research. Conclusion Challenges regarding the management of diabetes in Iran is multifaceted. Reforming the health care system or developing complementary strategies is essential to improve suitable health care model for patients with chronic conditions such as diabetic patients.